Application of Motifs Woodcarving in Preserving Its Authenticity in Istana Balai Besar, Kota Bharu Kelantan - Muhammad, Siti Aisyah; Mohd Rosdi, Normaisarah (International Journal of Integrated Engineering, 2023)
A palace is the legitimate house of a noble monarchy or excessive dignitary. The palaces of the Malay Kings are derived from the architecture of the Malay houses but in a larger scale. However, since it was a government palace, its structure had to be changed to accommodate its dual functional structure. In addition to accommodating the king, the palace also functions as a hub for administrative work. Therefore, traditional Malay royal palaces were decorated with carved decorative elements depicting intricate carvings in specific patterns, shapes, sizes and arrangements. Various sculptural elements with specific characteristics were created depending on their location and the shape of the palace. The woodcarving as embellishment was created at the palace to symbolize the king’s status. Motifs are considered one of the primary elements behind the creation of woodcarving and is visually incorporated into various arts and crafts categories. Motifs also plays an important role in a woodcarving composition. Therefore, this study aimed to present a research to explore the visual forms of motifs of the carved component in Istana Balai Besar, Kota Bharu, Kelantan. A qualitative research approach was used to collect data through an analytical review of measured drawings and reports of the Istana Balai Besar from the architecture gallery at the Universiti Malaysia Kelantan (UMK), interviews with previous local woodcarvers and site visits to the selected palace. The final model confirmed that there were four types of motifs, namely flora, geometry, cosmos features, and Arabic calligraphy carved in two and three compositions together with perforated and embossed types of forms and it can be concluded that the floral motifs are the types of motifs that dominated the woodcarving at Istana Balai Besar.